Force-induced retro-click reaction of triazoles competes with adjacent single-bond rupture - Neudecker, Tim; Dreuw, Andreas (Chemical science, 2017)
The highly controversial force-induced cycloreversion of 1,2,3-triazole, its well-known retro-click reaction, is shown to be possible only for 1,5-substituted triazoles, but competes with rupture of an adjacent single-bond. We draw this conclusion from both static and dynamic calculations under external mechanical forces applied to unsubstituted and 1,4- and 1,5-substituted triazoles. The JEDI (Judgement of Energy DIstribution) analysis, a quantum chemical tool quantifying the distribution of strain energy in mechanically deformed molecules, is employed to identify the key factors facilitating the force-induced retro-click reaction in these systems. For 1,4-substituted triazoles it is shown to be impossible, but the parallel alignment of the scissile bond in 1,5-substituted triazoles with the acting force makes it generally feasible. However, the weakness of the carbon-nitrogen bond connecting the triazole ring to the linker prevents selective cycloreversion.